N-type doping in CdO ceramics: a study by EELS and photoemission spectroscopy - Dou, Y; Egdell, R; Walker, T; Law, D; Beamson, G (1998)
Ceramic samples of yttrium- and indium-doped CdO (Cd 1-xY xO with 0≤x≤0.035 and Cd 1-xIn xO with 0≤x≤0.023) have been studied by electron energy loss spectroscopy (EELS) and ultraviolet and X-ray photoemission spectroscopy (UPS and XPS). Both In and Y act as efficient n-type dopants, although the carrier concentration is higher in In-doped material. The maximum surface plasmon loss energy in EELS is 0.66 eV in Y-doped samples and 0.72 eV for In-doped samples. Effective masses (m*) increase with increasing carrier concentration N and obey an approximately linear variation of the form m* = m* + cN, where c is a constant. UPS shows a well-defined conduction band feature for doped samples. A shift of the valence band edge towards high binding energy due to chemical doping was observed in He(I) UPS, which is confirmed by shifts of O 2p valence band features and Cd 4d core level peaks in high resolution XPS. However, the shifts are less than expected from the increased widths of the occupied part of the conduction band. This is due to shrinkage of the bandgap with doping. XPS demonstrates that there is pronounced surface segregation of dopant atoms. However, the segregated dopant atoms do not act as donor centres. © 1998 Elsevier Science B.V.